BUSINESS PLAN: feasibility analysis of a digital marketing and advertising company - Pandolfi, José Guilherme; dos Reis Lucente, Adriano; Claudio Pandolfi, Marcos Alberto; Chiuchi Magrini, Rosemary (Revista Interface Tecnológica, 2023)
This work aimed to develop a business plan to analyze the feasibility of implementing a company called m2a Marketing Digital e Propaganda, located in the city of Taquaritinga- SP, seeking to understand the behavior of potential customers. However, purchases of equipment for the company’s physical structure and the hiring of partners and employees with knowledge in the areas of activity were considered, analyzing the strengths and weaknesses of the business. Technical analysis methodologies were adopted with information gathering using data from bibliographic research, books and publications. The structure was based on organizational models, seeking to understand the functioning of a company in the Digital Marketing sector, where it was possible to conclude that the agency’s business plan presents a clear and strategic vision for the company’s development. It was also possible to identify market opportunities. The proposed marketing, operational and financial strategies are solid and aligned with the company’s short and long-term objectives. Financial analysis revealed realistic projections and key performance indicators that will enable ongoing monitoring and evaluation of business.